Analysis of the Relation Between the Relief and the Surface Water Network - Tomor, Tamás (Acta Agraria Debreceniensis, 2003)
The Bihar plain situated in the Great Hungarian Plain has altitudinal values between 87 and 108 meters above Baltic level and these low average values decreases from East to West. We can find on this place a surface water network with a high density; the most of them was created for diversion of inland water. The GIS is the best practice for modelling and simulating the relief and the water network. Towards the creation of the TIN model and relief- analysis we need the digital elevation model as well as the digital water network dataset for the whole territory. The source of the data was topographic maps on high scale level (1:10.000).